Sünnî-Şiî İkilemine Farklı Bir Bakış: Yeniden İnşa Edilen Hadis Bağlamları - (:unkn) unknown (My University, 2019)
Şiî cemaatlerin hicrî ilk üç asır boyunca İslâm toplumunun ana bünyesini teşkil eden ehl-i hadisten ayrışma ve mezhepleşme sürecinde yaşananlar sadece bir dinî yapının kimlik bulma süreciyle değil aynı zamanda Sünnî hadis tarihi ile de pek çok açıdan ilgilidir. Bu çalışma bir açıdan Sünnî-Şiî rivayet geçişkenliklerine dair birtakım yargılarda bulunsa da temelde rivayet geçişleri esnasında vuku bulan bağlam değişimlerini tespit etmeyi hedeflemektedir. Bu tespit, uydurma faaliyetleri ve meşru bir zemini bulunmayan tevil çabaları kadar olmasa da yeniden inşa edilen hadis bağlamlarının mezhebî kabulleri desteklemedeki rolü hakkında fikir verecektir. Bağlam değişimleri birden fazla surette gerçekleşmektedir. Öncelikle bir kaynaktaki rivayet, farklı bir kaynakta bambaşka bir arka plan bilgisiyle sunulabilmekte, uzun bir rivayetin bir kısmı ayrıştırılarak bir veya aynı anlatının içerisine yerleştirilen birden fazla rivayetle yan yana anılabilmekte veya aynı bağlamla aktarılsa da kendisine yüklenen yeni anlam dolayısıyla aslî kastından uzaklaşabilmektedir. Özellikle fezâil ve mesâlib türü rivayetler ile polemik türü anlatılar bu takibi yapmak açısından hayli işlevseldir. Mezkûr geçişkenliği temin eden ve büyük oranda Şiî eğilimlere sahip olmakla itham edilen râvilerin belirlenmesi ise Şiî cemaatlerin ehl-i hadisten bağımsız olarak ilim yapma becerisini kazanma dönemlerine ışık tutabilir.

The separation of the Shīʿīte community from the mainstream Sunnis is not solely relevant to the process of a sect’s identity-creation and systematization. Rather, this separation also influenced the study of ḥadīth during the second/eighth century. Throughout the second century, ḥadīth transmitters from the group of Ahl al-ḥadīth (People of tradition) and those from the Shīʿīte tradition participated within the same scholarly circles and attended classes taught by the same scholars. However, by the end of the second century and the beginning of the third century, Shīʿīte students were only able to continue their studies in Shīʿīte scholarly circles. Certain scholar-leaders, such as Jaʿfar al-Ṣādiq and Mūsā al-Kāẓim, contributed significantly to the identity creation of the community. During this process of separation, critics from Ahl al-ḥadīth reviewed the Shīʿīte-inclined transmitters in an increasingly negative tone. Further, every group that fell outside of the mainstream Muslim community participated, in one way or another, in fabricating traditions in order to legitimize their own positions. In addition to fabrications, alterations in contexts and alternative interpretations emerged in this period. Particularly, certain alterations occurred to the contexts of the transmissions by the Shīʿīte-inclined transmitters from Ahl al-ḥadīth circles to Shīʿīte circles. Although this article includes discussions on Sunnī-Shīʿīte narrative transitivity, it aims in particular to identify alterations to contexts during narrative transmissions or later stages._x000D_ _x000D_ It seems that reinvention or alteration to the contexts of prophetic traditions played a significant role in influencing sectarian principles, even if they cannot be compared with fabrications or ungrounded interpretations. When one examines in detail the traditions under the headings of virtues or defects, “reinvention of contexts” or “alterations of contexts” occur in three notable ways: 1- A tradition from a Sunnī source is transmitted to a Sunnī source or more generally to a Shīʿīte source with completely different background information; 2- A lengthy tradition in a Sunnī source is transmitted partially to a Shīʿīte source and that part is placed beside multiple transmission of the same narrative; 3- A tradition from both Sunnī and Shīʿīte sources is transmitted with a new meaning and loses its original sense, thereby supporting the sectarian position._x000D_ _x000D_ Identifying the period in which context alterations occurred and the actors responsible for the alterations is important to tracing Sunnī-Shīʿīte narrative transitivity. This article examines several traditions that exist in the sources of both schools and enable us to trace transitivity. It analyzes the traditions on “Hypocrite’s grudge and Muslim’s love”, “I am warrior” and “Alī’s gate” as examples of reinvented or altered contexts; and the traditions of “Twelve caliphs” and “May God make you proud” as examples of semantic shifts in meanings. Narrative transitivity and context alterations primarily occurred from the end of the second century and the beginning of the third century until the first half of the fourth century. This argument corroborates many parallel studies. Almost all of the individuals who were responsible from the narrative transitivity and context alterations were identified as transmitters from Kūfa who were accused of being Shīʿīte-inclined scholars. _x000D_ _x000D_ While identifying these transmitters, studying the chains of transmissions in alternative sources seems to be as useful as analyzing the texts of the traditions. In fact, some traditions are recorded in Shīʿīte sources with Sunnī chains of transmission until a specific generation, but then the names in the chains diverge from those that are found in Sunnī biographical dictionaries. Particularly, starting in the beginning of the third century, the proportion of Shīʿīte-inclined scholars in Sunnī chains decreases and Shīʿīte transmitters are mostly recorded in Shīʿīte biographical dictionaries. This is related to the fact that the transmitter, before whom are Sunnī authorities and after whom are Shīʿītes, can be held responsible for a particular ḥadīth’s transition into Shīʿīte sources and its context alterations. One should take into consideration both the transmitter’s Shīʿīte inclinations and the forms of recording by Shīʿīte scholars in order to identify responsibility for the context alterations in the second century._x000D_ _x000D_ Context alterations and changes to the texts of traditions seem to match up with Shīʿīte thought in this period. In fact, it is noteworthy that at a time before the theory of twelve imams was solidified, the tradition of “twelve caliphs” is not recorded in Shīʿīte sources. Similarly, in narrative transitivities during the second century, praises of Alī and the Prophet’s family as well as statements targeting his opponents could take more emphasized forms and some political implications might be added to the traditions. However, certain themes, such as chastity and return, which had a role in institutionalized Shīʿīsm were not included during this period. The investigation of changes in transmissions from this point of view can improve our understanding of the development of Imāmī Shīʿīsm._x000D_ _x000D_ The history of the early Sunnī tradition can only be understood by examining in detail the development of other sects/schools and their relations to the Sunnī community, because no religious school can be examined in isolation. This method seems to be difficult for certain schools such as Muʿtazila and Murjiʾa, but it fits well in terms of a parallel reading of Shīʿīte and Sunnī sources, because both have considerable scholarly accumulation. This kind of study will also enable us to understand dark spots in the activity of jarḥ-taʿdīl and the composition of books during the second and third centuries.
A New Look at Sunnī-Shīʿīte Sectarianism: Reinvented Contexts of Prophetic Traditions
Keywords: Din Bilimi